VD_FINDINFO HC / 2011 / 44 vom 9. November 2010 - VD Tribunal cantonal (2010)
APPRÉCIATION DES PREUVES, INTERDICTION DE L'ARBITRAIRE, LIMITATION AUX CONCLUSIONS DES PARTIES | 3 CPC, 4 CPC, 444 al. 1 ch. 3 CPC, 444 al. 2 CPC, 5 CPC